Prevalence of Gendered Views of Reading in Thailand and Canada - Sokal, Laura (Alberta Journal of Educational Research, 2010)
Recent large-scale testing of reading achievement indicates significant gender differences favoring girls in all countries tested, a situation that some researchers believe is the result of boys viewing reading as a feminine activity. Given that Canada has one of the world’s smallest gender gaps in reading whereas Thailand has one of the largest, a matched sample of 168 boys from Canada and Thailand were studied to examine potential differences in prevalence of viewing reading as feminine. Findings show no significant differences between boys in Canada and Thailand, which suggests that viewing reading as feminine is not at the root of gender differences in reading achievement. Other potential contributing factors, including culture, socioeconomic status, and interest are discussed.